Re-Assessing PK/PD Issues for Oral Protein and Peptide Delivery - Randall J. Mrsny; Tahir A. Mahmood (MDPI AG, 2021)
Due to a lack of safe and effective oral delivery strategies for most protein and peptide therapeutics, pharmaceutical drug developers have focused on parenteral routes to administer these agents. Recent advances in delivery technologies have now shown clinical validation for a few of these biopharmaceuticals following oral administration. While these initial opportunities have provided more than just a glimmer of hope within the industry, there are important aspects of oral biopharmaceutical delivery that do not completely align with pharmacokinetic (PK) parameters and pharmacodynamics (PD) outcomes that have been learned from parenteral administrations. This commentary examines some of these issues with the goal of presenting a rationale for re-assessing methods, models, and success criteria to better measure oral protein or peptide delivery outcomes related to PK/PD events.